Study of point defects in wide-bandgap Cu2CdGeS4 microcrystals by temperature and laser power dependent photoluminescence spectroscopy. (5th May 2020) - Krustok, Jüri; Raadik, Taavi; Li, Xiaofeng; Kauk-Kuusik, Marit; Timmo, Kristi; Oueslati, Souhaib; Grossberg, Maarja
Abstract: We present temperature and laser power dependent photoluminescence (PL) study of high quality wide-bandgap Cu2 CdGeS4 microcrystals. At T = 10 K three PL bands were detected at about 1.919 eV (#1), 1.855 eV (#2) and 1.748 eV (#3). The temperature and laser power dependencies indicate that the properties of PL bands can be explained by donor- acceptor pair model, where the #1 and #2 bands result from a recombination between distant pairs involving the same shallow acceptor VCu with EA ≍ 30 meV and different deep donor defects. The #3 PL band originates from the deep donor-deep acceptor pair recombination where the depth of deep acceptor defect is more than 157 meV. Detailed analysis of the PL spectra show the absence of deep potential or band gap fluctuations in this material making it suitable for photovoltaic applications.